Exploring how and why attributes of existing and emerging early cancer detection tests influence experiences and participation among individuals at risk of socioeconomic disadvantage: A qualitative interview study - Stefanie Bonfield; Evangelos Katsampouris; Suzanne E. Scott; Stephen W. Duffy; Fiona M. Walter; Samantha L. Quaife (PLoS ONE, 2025)
Background Emerging sample biomarker tests promise to improve early cancer detection, but also stand to influence socioeconomic inequalities in uptake of asymptomatic screening and symptomatic referrals. Objective To explore how and why different attributes of early cancer detection tests influence experiences and participation across test modalities and contexts among individuals at risk of socioeconomic disadvantage. Method Qualitative semi-structured interviews with 30 individuals (aged ≥50 years) at risk of socioeconomic disadvantage explored how and why different attributes of early cancer detection tests affected their experiences and participation across test modalities and contexts. Vignette test scenarios and a think-aloud protocol were used to facilitate interviewees’ deliberation between a range of test attributes. Data were analysed using framework analysis. Results Select attributes of early cancer detection tests prevented equitable access due to conflicts with lived experiences such as caring responsibilities, reduced mobility, concerns about being stigmatised, and not being physically or psychologically able to undergo procedures. Participants perceived more invasive forms of testing conducted by a doctor in a hospital to indicate greater risk of a cancer diagnosis, and higher perceived risk of cancer was associated with preferences for attributes perceived to deliver an accurate or quick result. Participants varied in what they considered a ‘cancer test’ and some did not want to test due to the perceived or experienced burden of waiting for or receiving a cancer result. Conclusions Emerging sample tests to support early cancer detection could address existing barriers to uptake by offering greater convenience. Inequitable uptake may persist if individuals do not perceive there to be a sufficient reason to test, are not confident to take part or doubt the ability of sample tests to accurately detect signs of cancer.